The influence of different shades and brands of resin-based luting agents on the final color of leucite-reinforced veneering ceramic - Rashin Giti; Amirhossein Barfei; Mina Mohaghegh (Elsevier, 2019)
Objectives: This study aimed to evaluate the influence of different shades and brands of resin-based luting agents on the final color of a leucite-reinforced veneering ceramic. Methods: This in-vitro study was done on 36 ceramic discs (IPS Empress I, 11 × 0.5 mm, A2 shade) and 36 cement disks (11 × 0.2 mm) made of Panavia SA Cement Plus (Kuraray Medical Inc.) and Choice2 (Bisco Inc., Schumburg) brands in translucent, universal A2, and opaque shades (n = 6 per each color in each resin cement brand). Color parameters (CIEL*a*b*) of ceramic specimens were calculated without and with each brand/shade of resin-based luting agents by using a spectrophotometer, and put into CIELab formula. The color differences (ΔE) between the two sets of measurements were calculated and analyzed with two-way ANOVA and Tukey's post hoc test (α = 0.05). Results: Both the resin-based luting agent shade (P < 0.001) and brand (P = 0.023) significantly affected the color differences. ΔE values were significantly different between Panavia-opaque and Choice2-opaque (P < 0.001). No significant difference existed between ΔE of the two brands in A2 (P = 0.178) and translucent shades (P = 0.079). The ΔE values of Panavia-A2 was significantly different from the translucent and opaque shades of the same brand. Moreover, the ΔE of Choice2-translucent shade was significantly lower than that of A2 and opaque shades. The ΔE values were higher than the clinically-acceptable threshold in all groups (ΔE > 3.7) except for Choice2-translucent (ΔE = 3.37). Conclusions: The final color of leucite-reinforced veneering ceramic can be affected by the same shades of resin-based luting agents from different brands and different shades of resin-based luting agents from the same brand. Keywords: Color difference, Resin shade, Ceramic veneer